2000
DOI: 10.1128/aem.66.6.2678-2681.2000
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Siderophore and Hemolysin from Stachybotrys chartarum Strains, Including a Strain Isolated from the Lung of a Child with Pulmonary Hemorrhage and Hemosiderosis

Abstract: A strain of Stachybotrys chartarum was recently isolated from the lung of a pulmonary hemorrhage and hemosiderosis (PH) patient in Texas (designated the Houston strain). This is the first time that S. chartarum has been isolated from the lung of a PH patient. In this study, the Houston strain and 10 strains of S. chartarum isolated from case (n ‫؍‬ 5) or control (n ‫؍‬ 5) homes in Cleveland were analyzed for hemolytic activity, siderophore production, and relatedness as measured by random amplified polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Previously it was shown that all strains used in this study, when grown on SBA or TSB with blood, produced a hemolytic agent (35,36). If blood is not added to the TSB, most strains isolated from the homes of infants with PH and the Houston strain isolated from the lung of a PH victim still produced stachylysin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously it was shown that all strains used in this study, when grown on SBA or TSB with blood, produced a hemolytic agent (35,36). If blood is not added to the TSB, most strains isolated from the homes of infants with PH and the Houston strain isolated from the lung of a PH victim still produced stachylysin.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of S. chartarum isolated from PH case houses in Cleveland, Ohio (18), and the isolate from the lung of a PH patient in Texas (9) generally produced significantly more hemolysin under the conditions tested than most strains isolated from control houses in Cleveland (36). In this report, an explanation for the hemorrhaging after S. chartarum exposure is suggested, based on the role of stachylysin in vascular leakage in a model organism, Lumbricus terrestis.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The correlation between S. chartarum and acute idiopathic pulmonary hemorrhage-hemosiderosis has recently been questioned (1,8), but simultaneously experimental lung mycotoxicosis was found in mice exposed to spores of S. chartarum (13). S. chartarum produces several mycotoxins, immunosuppressive agents, and hemolysin activity (9,18). We hypothesized that this fungal pathogen might also produce proteinases that could lead to destruction of lung tissue.…”
mentioning
confidence: 99%